Actividad peroxidasa y concentración de proteínas en Phaseolus vulgaris l. tratado con preparaciones homeopáticas (Research, Society and Development, 2021)
The objective of this work was to evaluate peroxidase activity and protein concentration in the defence system expression of common bean Phaseolus vulgaris L., submitted to different potencies of homeopathic preparations. The treatments were composed by: Arsenicum album, Staphisagria, Silicea and Sulphur, in the 6, 12 and 18 CH potencies, compared to the controls. The bean seeds were sown in pots which were kept in a greenhouse and the treatments were applied to them at 1% in distilled water since the sowing day, with intervals of 15 days until the R7 stage. The first evaluation was performed at 15 e 60 days after sowing, after artificial mechanical damage. Protein concentration and the activity of guaiacol peroxidase (POD) and ascorbate peroxidase (APX) enzymes were determined. Differences between treatments and controls were estimated by Glass Delta effect size analysis. Staphisagria 12CH induced greater increase in protein concentration on bean leaves. The Induction on APX and POD activities were observed in leaves treated with Sulphur in all tested potencies. The Glass Delta effect showed undulatory behaviour, sometimes acting positively, sometimes negatively, throughout all evaluations. Homeopathic preparations have the potential to induce biochemical defence mechanisms in beans, acting as resistance elicitors.